Cyanides, Isocyanides, and Hydrides of Zn, Cd and Hg from Metal Atom and HCN Reactions: Matrix Infrared Spectra and Electronic Structure Calculations. Issue 18 (13th August 2021) - Li, Hongmin; Tsegaw, Yetsedaw A.; Andrews, Lester; Trindle, Carl; Cho, Han‐Gook; Stüker, Tony; Beckers, Helmut; Riedel, Sebastian
Abstract: Zinc and cadmium atoms from laser ablation of the metals and mercury atoms ablated from a dental amalgam target react with HCN in excess argon during deposition at 5 K to form the MCN and MNC molecules and CN radicals. UV irradiation decreases the higher energy ZnNC isomer in favor of the lower energy ZnCN product. Cadmium and mercury atoms produce analogous MCN primary molecules. Laser ablation of metals also produces plume radiation which initiates H‐atom detachment from HCN. The freed H atom can add to CN radical to produce the HNC isomer. The argon matrix also traps the higher energy but more intensely absorbing isocyanide molecules. Further reactions with H atoms generate HMCN and HMNC hydrides, which can be observed by virtue of their C−N stretches and intense M−H stretches. Computational modeling of IR spectra and relative energies guides the identification of reaction products by providing generally reliable frequency differences within the Zn, Cd and Hg family of products, and estimating isotopic shifts using to 13 C and 15 N isotopic substitution for comparison with experimental data. Abstract : Matrix infrared spectra : Outline of the reactions that occur with laser ablated Hg atoms and HCN molecules during condensation in excess argon at 5 K and subsequent annealing to allow diffusion and reaction of H atoms with the HgCN and HgNC primary reaction products to form their hydrides.